Anaerobic Exercise-Induced Activation of Antioxidant Enzymes in the Blood of Women and Men - Wiecek, Magdalena; Szymura, Jadwiga; Maciejczyk, Marcin; Kantorowicz, Malgorzata; Szygula, Zbigniew (Frontiers in Physiology, 2018)
Objective Physical exercise changes redox balance in the blood. The study aim is to determine gender-related differences in enzymatic antioxidant defence (superoxide dismutase, catalase, glutathione peroxidase) in the early period following anaerobic exercise and 24 hours after its completion. Methods Young, non-training participants (10 women and 10 men) performed a single anaerobic exercise, which was a 20-second maximal cycling sprint test. Blood was collected before beginning and after completing the anaerobic exercise i.e. after 3, 15, 30 and 60 minutes and after 24 hours. Lactate concentration, and the superoxide dismutase, catalase and glutathione peroxidase activity were determined. The results were adjusted to the changes in plasma volume. Results Anaerobic exercise induced a significant increase in lactate concentration similar among both sexes. Anaerobic exercise evokes identical changes in the activity of antioxidant enzymes in the blood plasma of women and men, which is dependent on anaerobic capacity. In the early phase of restitution, the activity of antioxidant enzymes decreases. 24 hours after anaerobic exercise, glutathione peroxidase activity in the blood plasma of women and men is higher than before the exercise. Conclusions There are no gender-related differences in changes in plasma antioxidant activity after anaerobic exercise. Depending on the antioxidant enzyme, changes of activity differ in time after the end of the anaerobic exercise.